2010
DOI: 10.1038/jes.2010.8
|View full text |Cite
|
Sign up to set email alerts
|

“Dirty electricity”: what, where, and should we care?

Abstract: Environmental exposure to high-frequency voltage transients (HFVT), also termed dirty electricity, has been advocated among electro(hyper)sensitive interest groups as an important biological active component of standard electromagnetic pollution. A literature search was conducted in PubMed, in which only seven articles were identified. Exposure to HFVT was associated with increased cancer risks, while preferential removal of 4-100 kHz HFVT from 50-60 Hz ELF circuits was linked to a variety of improvements in h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…One paper was retracted by the journal because of absence of ethical approval ( 34 ). Of the 25 remaining papers, one review, by one of the authors of this paper, reviewed primary data published up to July 31, 2009, which included seven published, peer-reviewed journals papers ( 35 ). The literature base for the present review includes an additional 18 publications, published either as conference abstracts prior to the initial review cut-off or published after the July 31, 2009 cut-off date, and now includes the total evidence base of 12 peer-reviewed journal and conference abstract publications of which three are reviews and three are exposure studies only, seven conference abstracts, one editorial mentioning DE, and six letters to various editors.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…One paper was retracted by the journal because of absence of ethical approval ( 34 ). Of the 25 remaining papers, one review, by one of the authors of this paper, reviewed primary data published up to July 31, 2009, which included seven published, peer-reviewed journals papers ( 35 ). The literature base for the present review includes an additional 18 publications, published either as conference abstracts prior to the initial review cut-off or published after the July 31, 2009 cut-off date, and now includes the total evidence base of 12 peer-reviewed journal and conference abstract publications of which three are reviews and three are exposure studies only, seven conference abstracts, one editorial mentioning DE, and six letters to various editors.…”
Section: Resultsmentioning
confidence: 99%
“… a (*) indicating publication was included in 2010 review in Ref. ( 35 ) . b Duplicate reporting of case studies has never been reported by authors, and identification has been done here based on similarities in case descriptions .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In citing previous work, Dr. Milham did not include a systematic review in which all available evidence was reviewed by de Vocht (2010). The review concluded that the few studies that were done, mostly by the same researchers, were all subject to methodological problems large enough to prohibit valid assessment of any biological activity of HFVT.…”
Section: 1mentioning
confidence: 99%